Evaluation of Running Water Rinsing of Soft Contact Lenses - Shih, K; Hu, J; Sibley, M.J (Canadian Journal of Optometry, 2021)
The safety of using running water to rinse soft contact lenses was evaluated. Twenty soft contact lenses were contaminated with viable microorganisms in an organic load and were then rinsed under running water for 20-30 seconds. The results showed that the reduction of the contaminants by the running water rinsing alone was always more than 98%. To evaluate the contaminant level introduced to the lenses by the running water, 24 sterile lenses were also rinsed with running water. Our results indicated that these lenses were virtually not contaminated with running water rinsing. However, when 30 sterile lenses were handled by 15 soft contact lens wearers in the same manner as they would prior to inserting the lenses in their eyes, thousands of contaminants were recovered per lens in average. Furthermore, when lenses containing different water levels were rinsed in water, followed by soaking in a sterile isotonic saline solution, none of the lenses were adversely affected physically by the water rinse. From the results of this study, we believe that it is safe to use running water to rinse soft contact lenses in conjunction with a safe holding device and a proper disinfecting regimen.